Bacillus asahii comes to the fore in organic manure fertilized alkaline soils. (February 2015) - Feng, Youzhi; Chen, Ruirui; Hu, Junli; Zhao, Fei; Wang, Junhua; Chu, Haiyan; Zhang, Jiabao; Dolfing, Jan; Lin, Xiangui
Abstract: Organic manure (OM) fertilization has a profound impact on agroecosystems. However, little is known about temporal responses and roles of the specific soil microbial guilds involved in the increases of soil fertility and crop yield triggered by OM fertilization. To unravel these interactions, a series of fresh and archived soil samples from a fertilization experiment started in 1989 in North China Plain (NCP) was systematically investigated. Molecular assays of contemporary fresh samples unravel that Bacillus asahii responded most distinctly to OM fertilization, while no shifts in microbial community structure were observed between chemical fertilizations and the control without fertilization; a series of archived soil samples from 1989 to 2009 reveal that the indigenous B . asahii took 2–4 years to become specifically dominant and its ratio fluctuated between 40% and 72% during 20 years. Culture-dependent assessments of isolated B . asahii strain further indicate that its rise subsequently played a key role in the increases of both crop yield and soil fertility, especially via accelerating carbon and phosphorus cycling. This insight deepens our understanding of how OM impacts agroecosystems through soil microbial processes, and highlights the possibility of using archived microbial information as a reference to develop an efficient and sustainable agricultural strategy. Highlights: Bacillus asahii responds most distinctly to long-term organic manure (OM) fertilization. Indigenous B. asahii takes 2–4 years to become dominant in OM fertilized soils. Increase of B. asahii plays a key role in promoting crop yield and soil fertility. Archived soils can be a source of valuable microbiological information.